The fiscal compact and government debt: One law, multiple statistics - I\~naki Aldasoro; Ester Faia (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
In many cases, the dire situation of public finances calls into question the very soundness of sovereigns and prompts corrective actions with far-reaching consequences. In this context, European authorities responded with several measures on different fronts, for instance by passing the "Fiscal Compact", which entered into force on January 1, 2013. Of critical importance in this framework is the assessment of a country's situation by way of statistical measures, in order to take corrective actions when called for according to the letter of the law. If these statistics are not correct, there is a risk of imposing draconian measures on countries that do not really need it.
urn:nbn:de:hebis:30:3-336398
Keywords: 330; government debt; statistics; Fiscal Compact